Phylogenetic relationships of lizards of the Liolaemus petrophilus group (Squamata, liolaemidae), with description of two new species from western Argentina - Avila, Luciano Javier (2004)
We describe two new species of lizards of the genus Liolaemusfrom western Argentina. Bothspecies belong to the petrophilus group and are easily distinguished from other members by a combination ofchromatic and squamation characters. We used sequences of the mitochondrial cyt–b, 12S, and ND4 and thenuclear C–mos genes to infer the phylogeny of described species of the group. We found evidence for a monophyletic petrophilus group within theL. elongatus–kriegicomplex. The petrophilusgroup includes Liolaemus petrophilusand two strongly supported clades, one containing the species distributed in the north,which includes one of the new species,L. talampaya; the second clade includes the species distributed in thesouth, including the new species,L. gununakuna.